Taxation without Representation? : Experimental Evidence from Ghana and Uganda on Citizen Action toward Taxes, Oil, and Aid - de la Cuesta, Brandon (World Bank, Washington, DC, 2017)
Seminal arguments in political economy hold that citizens will more readily demand accountability from governments for taxes than for non-tax revenue from oil or aid. Two identical experiments on large, representative subject pools in Ghana and Uganda probe the effects of different revenue types on citizens' actions to monitor government spending. Roughly half of all subjects willingly sign petitions and donate money to scrutinize all three sources. However, neither Ghanaians nor Ugandans are more likely to take action for tax revenues than for oil or aid. The results also suggest no differences among taxes, oil, and aid in citizens' perceptions of transparency, misappropriation risk, or public goods provision. The results are robust to several alternative specifications and subgroup partitions, including the better educated, wealthier, and taxpaying population, suggesting a need for rethinking the axiom that taxation strengthens citizens' demands for accountability in developing countries.